The Recommendations for the Management of Chinese Children With Epilepsy During the COVID-19 Outbreak - Baiyu Chen; Baiyu Chen; Miriam Kessi; Miriam Kessi; Shimeng Chen; Shimeng Chen; Juan Xiong; Juan Xiong; Liwen Wu; Liwen Wu; Xiaolu Deng; Xiaolu Deng; et al. (Frontiers Media S.A., 2020)
The coronavirus disease (COVID-19) is the most severe public health problem facing the world currently. Social distancing and avoidance of unnecessary movements are preventive strategies that are being advocated to prevent the spread of the causative virus [severe acute respiratory syndrome (SARS)-CoV2]. It is known that epileptic children need long term treatments (antiepileptic drugs and/or immunosuppressive agents) as well as close follow up due to the nature of the disease. In addition, it is clear that epilepsy can concur with other chronic illnesses which can lower body immunity. As a result, epileptic children have high risk of acquiring this novel disease due to weak/immature immune system. Of concern, the management of children with epilepsy has become more challenging during this outbreak due to the prevention measures that are being taken. Although children with controlled seizures can be managed at home, it is challenging for pediatricians when it comes to cases with uncontrolled seizures/severe cases. To this end, we provide recommendations for the management of epileptic children at home, outpatient and inpatient settings.